Manufacturing of Al-Zr-Si master alloy from zircon concentrate - Khanh, Huynh Cong; Phap, Ly Thai; Toan, Do Thanh (Vietnam Journal of Science and Technology, 2024)
Aluminum alloy of thermal-resistant aluminum alloy wire for overhead line conductors usually contains zirconium, silicon, iron, and other components. Hence, Al-Zr-Si master alloy can be used to produce thermal-resistant aluminum alloy. In this study, the manufacturing procedure of Al-Zr-Si master alloy from zircon concentrate has been introduced. The zircon concentrate was thoroughly mixed with different amounts of KCl and Na2SiF6 or Na3AlF6, then sintered in the electric muffle furnace at 700oC for 2 hrs with automatic temperature control. The sinter was premixed with Na3AlF6 at the 1:1 ratio and dried at 140-160oC to remove the humidity. The powder mixture was added to the aluminum molten at 1200oC and then stirred well to ensure proper powder mixing in the melt. After the finish reaction and slag skimming, the melt was taken out of the furnace and poured into the mold. The master alloy was characterized by a Spectrometer, ICP-OES, and optical microscopy.